Buoyancy Distribution Model and Cumulative Buoyancy of Shield Tunnel Considering Time-Varying Properties of Slurry - CAO Yang; ZHANG Chaoyu; LIU Yang; LI Guozheng (工程科学与技术)
During the construction of shield tunnels, the upward floating deformation of tunnel structures caused by the combined action of the liquid buoyancy and the grouting pressure of the shield tail grouting layer has become a prominent engineering concern in such underground projects. The upward floating of shield tunnels due to shield tail synchronous grouting was studied. On the premise of distinguishing static and dynamic buoyancy, a static buoyancy model test was designed and carried out, in which the time-varying characteristics of slurry during solidification were considered, and the changing trend of static buoyancy with the increase of slurry viscosity was analyzed. In accordance with the basic physical tenet of Archimedes' law of liquid buoyancy, the mathematical expression of static buoyancy of the target slurry at each moment was obtained through fitting methods. To obtain the dynamic buoyancy of the grouting layer related to construction parameters, the grouting model test was conducted to provide calibration data for the numerical model before the establishment of a shield tail grouting model using the discrete element method. In the grouting model test, the time-varying characteristics of slurry was also taken as the basic control condition, and the slurry diffusion law in sand strata was summarized on the basis of slurry permeation distance and corresponding grouting pressure dissipation. Furthermore, a comparative model of the grouting test was established using the discrete element method. The particle meso-contact parameters in the numerical model were calibrated according to the test results, which were utilized to establish a numerical simulation model for synchronous grouting of the shield tail with continuous-discrete coupling, so as to observe the diffusion law of slurry in the shield excavation gap and the surrounding strata, and clarify the dynamic buoyancy distribution pattern of the shield tunnel while considering the impacts of slurry solidification and grouting pressure. Finally, the floating calculation model of the new shield tunnel was established with the finite element method. The cumulative floating effect of the tunnel structure within the effective influence range was analyzed based on the time-space gradual law of the two kinds of buoyancy caused by the synchronous grouting of the shield tail. The results show that the slurry viscosity increased exponentially with the solidification time, and the slurry used for shield tail grouting attained a relatively higher solidification level at 180 minutes. The subsequent viscosity variation trend could be predicted using the fitting curve. Slurry solidification led to fluidity loss, and a corresponding decrease in both static and dynamic buoyancy of the grouting layer. Additionally, as the slurry fluidity experienced a pronounced reduction in the initial stage, the buoyancy diminished at a higher rate during this stage. According to the buoyancy coefficient, the final reduction in dynamic buoyancy was obviously greater than that of static buoyancy. The static buoyancy of the slurry conformed to the general liquid buoyancy principle and was affected by the time-varying properties of the material. This buoyancy plummeted to 65% of the initial value within the first hour, and then gradually stabilized at 53% as time goes by. During the grouting process, the pressure within the grouting pipes at the lower side of the shield tunneling machine was marginally higher than that of the upper pipes, prompting slurry particles to gravitate towards the lower part of the excavation gap under the influence of gravity. Hence, the grouting pressure around the tunnel was distributed with a minor upward and a significant downward, and the resultant force was the upward-directed dynamic buoyancy exerted on the structure. Due to the large porosity of the sand strata, the slurry permeated rapidly into the surrounding strata under the action of the internal pressure of the grouting layer, which considerably reduced the grouting layer pressure. This is the primary reason why the reduction rate and degree of the dynamic buoyancy exceed that of the static buoyancy mentioned above. The dynamic buoyancy plummeted to 31% of the initial value within half an hour and eventually stabilized gradually at 28% of the initial value. If the construction parameters were adjusted, the dynamic buoyancy of the grouting layer would increase with the grouting pressure. Under the influence of the upward slurry buoyancy, the growth pattern of the upward displacement of the single ring of shield tunnel exhibits a convex-upward tendency, that is, the tunnel ring newly detached from the shield tail was subjected to considerably large total upward buoyancy, and the structure experiences a relatively rapid floating rate. As the buoyancy dissipated, the upward deformation of the structure gradually became stable. Since all the tunnel rings underwent the same uplifting process after detaching the shield tail, the overall structural deformation within the buoyancy gradient range behind the shield machine also presented a convex-upward shape. Greater grouting pressure led to a more significant cumulative upward floating of the structure, increasing linearly with the grouting pressure. In summary, to effectively control the upward deformation of shield tunnel during the construction, it is necessary to select appropriate slurry materials according to stratum types, and rationally regulate the time-varying viscosity of slurry in the early solidification stage, and then cooperate with the optimization of construction parameters to achieve effective control of the floating.